Edukasi Pentingnya Nutrisi terhadap Ibu Hamil sebagai Upaya Pencegahan Stunting di Desa Lemahbang - Purwanta; Probo Saraswati; Putri Azzara; Rozin Dwi Salim; Fatkhul Falestine; Ridha Prabawati; Faiza Husnia (Direktorat Pengabdian kepada Masyarakat, 2023)
The prevalence of stunting in Wonogiri Regency is classified as relatively high. The first 1000 days of life is the golden period that determines the child's future life. Knowledge about nutrition at this period is important to prevent stunting. The 1000 days of life education program aims to increase the knowledge of pregnant women about their nutritional needs, pregnancy well being, hygiene, and environmental conditions. In this program, quantitative research was carried out with experimental method using pre-experimental designs and the design model applied is one-group pretest-posttest design with paired sample t-test analysis. The results showed that there is an effect of the 1000 days of life education program on the knowledge of pregnant women in Lemahbang Village as evidenced by the significant difference in the average pretest and posttest results that have been held. In this study, results obtained a p-value of 0.003 or <(0.005). This educational program is important to be implemented continually to increase the knowledge of pregnant women regarding the importance of nutrition at 1000 days of life as a prevention of stunting.